The Effect of Problem Based Learning Model Using PhET Simulation Media Integrated with Scientific Literacy to Improve Learning Outcomes. - Panesya Septia Hendika sinaga; Gulmah Sugiharti (Universitas Lampung, 2026)
This study aimed to determine the effect of the Problem Based Learning (PBL) model using PhET Simulation media and scientific literacy skills on students’ chemistry learning outcomes in acid-base material. The study employed a quasi-experimental method with a 2×2 factorial design conducted at SMA Negeri 10 Medan in the 2025/2026 academic year. The samples consisted of two classes: a class taught using the PBL model assisted by PhET Simulation and a class taught using the Direct Instruction model with real laboratory media. Data were collected through learning outcome tests and scientific literacy tests, then analyzed using two-way ANOVA at a significance level of 0.05. The results showed that the learning model using media, scientific literacy skills, and their interaction significantly affected students’ chemistry learning outcomes in acid-base material. Therefore, the implementation of the PBL model assisted by PhET Simulation was effective in improving students’ chemistry learning outcomes.